2015
DOI: 10.1002/ptr.5353
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Plant Derivatives against Acrylamide Neurotoxicity

Abstract: Certain industrial chemicals and food contaminants have been demonstrated to possess neurotoxic activity and have been suspected to cause brain-related disorders in humans. Acrylamide (ACR), a confirmed neurotoxicant, can be found in trace amount in commonly consumed human aliments as a result of food processing or cooking. This discovery aroused a great concern in the public, and increasing efforts are continuously geared towards the resolution of this serious threat. The broad chemical diversity of plants ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 101 publications
(137 reference statements)
3
17
0
Order By: Relevance
“…In the present study, we demonstrated the anti-apoptotic, antioxidant and anti-in ammatory effects of curcumin on ACR-induced neurotoxicity in rats, suggesting the use of curcumin to prevent or delay neurological damages induced by ACR exposure. In line with the evidences from humans and animals [4,5,8,[11][12][13][14], our study showed that the 4-week exposure of rats to ACR at the dose of 40 mg/kg caused a signi cant body weight loss, progressive de cits in motor function and adverse pathological outcome in the cortex and hippocampus of rats. Importantly, the present data revealed that curcumin administration could e ciently rescue ACRinduced weight loss and neurobehavioral de cits, relieve the neuropathological damages in brain.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, we demonstrated the anti-apoptotic, antioxidant and anti-in ammatory effects of curcumin on ACR-induced neurotoxicity in rats, suggesting the use of curcumin to prevent or delay neurological damages induced by ACR exposure. In line with the evidences from humans and animals [4,5,8,[11][12][13][14], our study showed that the 4-week exposure of rats to ACR at the dose of 40 mg/kg caused a signi cant body weight loss, progressive de cits in motor function and adverse pathological outcome in the cortex and hippocampus of rats. Importantly, the present data revealed that curcumin administration could e ciently rescue ACRinduced weight loss and neurobehavioral de cits, relieve the neuropathological damages in brain.…”
Section: Discussionsupporting
confidence: 87%
“…Accordingly, in recent years, some agents with anti-apoptosis, antioxidant and anti-in ammatory properties have been expected to attenuate ACR-induced neurotoxicity [3,8,[11][12][13][14]. As the most active constituent in turmeric, a common spice, with a strong safety record, curcumin has been considered to be a potential natural neuroprotective agent under limelight [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Acrylamide (AA) has received great attention in recent years because it has proven to produce neurotoxic effects in animals and humans, reproductive and genotoxic outcomes in rodents, and mutagenicity in somatic cells in vitro and in vivo (Adewale et al, 2015;Kim et al, 2015). Additionally, AA was classified by the International Agency for Research on Cancer (IARC) as probably carcinogenic to humans (Oracz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…ACR conjugates with reduced glutathione (GSH) as the main antioxidant for detoxification. The ability of ACR to decrease antioxidant levels could be related, directly or indirectly, to its free-radicalproduction ability, thus leading to oxidative stress (3).…”
Section: Discussionmentioning
confidence: 99%
“…It also has an important application in laboratory research for the gel electrophoretic separation of molecules. Because of its wide application, people experience high levels of exposure (3). Additionally, ACR has been found in various thermally processed foods, such as potato chips, biscuits, and coffee.…”
Section: Introductionmentioning
confidence: 99%